Analysis of Heat Transfer Effectiveness Using A Plate Heat Exchanger in the Pasteurization Process at PT. XYZ - Ramadhan, M. Keitaro; Sumarjo, Jojo; Ujiburrahman, Ujiburrahman; Santoso, Deri Teguh (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
Pasteurization is a critical process in ice cream production to ensure product safety by eliminating pathogenic microorganisms, in which the Plate Heat Exchanger (PHE) plays a vital role in heat transfer efficiency. Inefficient heat transfer can reduce product quality and increase energy consumption. This study aims to evaluate the thermal performance and effectiveness of the PHE used in the pasteurization process at PT XYZ. The research method employed is quantitative analysis based on operational data collected over a 30-day period, including inlet and outlet temperatures, mass flow rates, and thermophysical properties of the ice cream mix and heating water. Heat transfer analysis was conducted using theoretical calculations of heat transfer rate, Log Mean Temperature Difference (LMTD), overall heat transfer coefficient, and heat exchanger effectiveness. The results indicate that the PHE operates with high thermal efficiency, achieving effectiveness values ranging from 90% to 99%, with an average effectiveness exceeding 94%. Optimal operating conditions were achieved when the PHE plates were fully supplied with circulating hot water, resulting in minimal heat transfer resistance. In contrast, efficiency reductions occurred during operating periods close to the Cleaning in Place (CIP) process, which led to a decrease in the overall heat transfer coefficient, as well as during transient operating conditions where large initial temperature differences between the product and heating water prevented optimal heat transfer. These findings demonstrate that the PHE performs effectively and meets operational standards for pasteurization in ice cream production processes.